Nutrition and Diet Factors in Type 2 Diabetes - Hana Kahleova (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
We are experiencing a worldwide epidemic of diabetes. Diabetes mellitus has become a major public health burden. Approximately seven million people develop diabetes in both developed and developing countries every year, with the most dramatic increases occurring in Type 2 Diabetes. Especially alarming, is the rising incidence of Type 2 Diabetes in obese children before puberty. In April 2017, a Special Issue of Nutrients entitled "Nutrition and Diet Factors in Type 2 Diabetes" closed with 19 published papers-eight original studies on humans, five on animals, one brief report and five reviews. The focus of the issue was on nutrition, diet factors, whole foods, broad dietary and lifestyle strategies, dietary patterns, intensive personalized treatments, nutritional prevention programs, and food policies that can be used in the development, treatment, and prevention of DM2. Nutrition and Diet Factors in Type 2 Diabetes is written for clinical and academic nutritionists, for registered dietitians, health professionals, graduate students, and for everybody with deeper interest in diabetes care. Studies and reviews presented here demonstrate that diabetes research is extensive and vibrant and the prevention, treatment and reversal of diabetes are achievable, economical, powerful, and possible.